Complete sequence analyses show that two defective interfering influenza viral RNAs contain a single internal deletion of a polymerase gene. - Nayak, D P (1982)
Defective interfering (DI) influenza viral RNAs arise by internal deletion of progenitor RNAs. By using recombinant DNA cloning and DNA sequence analysis techniques, we have deduced the complete sequence of two such RNAs (L2b and L3), both arising from the same polymerase (P1) gene of WSN influenza virus. We have also partially determined the sequence of the P1 polymerase gene, including the sequence at the point of deletion and the flanking regions. Our sequence study shows the following. (i) Both L2b and L3 arise by a simple deletion in the P1 gene. (ii) L2b and L3 are 683 and 441 nucleotides long, respectively. (iii) The first 413 and 244 nucleotides of the 5' ends of L2b and L3, respectively, are identical to those of the 5' end of the P1 gene. (iv) The last 270 nucleotides of L2b and 197 nucleotides of L3 are the same as those of the 3' end of the P1 gene. (v) The entire sequence of L3 is present in the sequence of L2b. (vi) Both the 5' and the 3' termini, including the transcription stop and poly(A) addition signals of the progenitor P1 gene, are present in both L2b and L3. (vii) The sequences at the deletion point and the flanking region of the P1 gene do not resemble the consensus splicing sequence of spliced mRNA suggesting that a replicational event rather than splicing is involved in the formation of influenza defective interfering RNAs.